Improving Mathematics Learning Outcomes Through Contextual Teaching Learning (CTL) Models with Auxiliary Objects of the Surrounding Environment at Madigondo Samigaluh Public Elementary School, Kulon Progo Regency, 2021/2022 Academic Year - Fembri Susilawati (Universitas Islam Indonesia, 2023)
This research was conducted to improve mathematics learning outcomes in the 2019 Coronavirus Disease (Covid-19) pandemic era through face-to-face meetings, increase student motivation in learning and improve teachers' abilities in carrying out teaching and learning activities. This type of research is Classroom Action Research (CAR). The subjects of this study were all fifth-grade students at SD Negeri Madigondo Kapanewon Samigaluh for the 2021/2022 academic year, with a total of 14 students consisting of 9 boys and 5 girls. The object of research is solving problems related to learning mathematics by using the CTL learning model to increase student motivation and achievement as well as teaching abilities in teaching and learning activities. The data collection technique in this study used the evaluation of student test assessments and observation sheets. The results showed that there was an increase in students' mathematics learning outcomes through the CTL learning model, namely in cycle I for 1st meeting of 55.56% in the